2022
DOI: 10.1038/s41598-022-17786-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oceanographic environment on the distribution and migration of Pacific saury (Cololabis saira) during main fishing season

Abstract: The Pacific saury (Cololabis saira) is one of the most commercially important pelagic fishes in Asia–Pacific countries. The oceanographic environment, especially the Oyashio Current, significantly affects the distribution of Pacific saury, and may lead to variations in their migration route and the formation of fishing grounds in Japanese coastal region and the high seas. In this study, six oceanographic factors, sea surface temperature (SST), sea surface chlorophyll-a concentration (SSC), sea surface salinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In particular, the Isoguchi Jet (Isoguchi et al 2006), which is a quasi-stationary jet that separates from Kuroshio currents and extends northward, has a strong influence on the feeding environment for pelagic fishes in this area (Miyamoto et al 2022). Various environmental factors that were suggested to be important for the distribution of Pacific saury, such as SSS, SSH, SSTG, and chl a, should be related to currents in this area (Chang et al 2019, Hua et al 2020, Liu et al 2022, Xing et al 2022). Long-term interannual variations in the current speed of the Isoguchi Jet (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, the Isoguchi Jet (Isoguchi et al 2006), which is a quasi-stationary jet that separates from Kuroshio currents and extends northward, has a strong influence on the feeding environment for pelagic fishes in this area (Miyamoto et al 2022). Various environmental factors that were suggested to be important for the distribution of Pacific saury, such as SSS, SSH, SSTG, and chl a, should be related to currents in this area (Chang et al 2019, Hua et al 2020, Liu et al 2022, Xing et al 2022). Long-term interannual variations in the current speed of the Isoguchi Jet (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Tseng et al 2013, Chang et al 2019, Hua et al 2020, Hsu et al 2021. In recent years, some studies have compared the relative importance of various environmental variables on Pacific saury distribution and found that SST and SSTG are more influential than other factors (Chang et al 2019, Liu et al 2022Xing et al 2022. Hence, we focused on the distribution pattern of Pacific saury and other species along the SST gradient in this study because SST is one of the most important factors explaining the distribution of not only Pacific saury (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a case, we should have observed latitudinal lines with a more gradual slope in summer and a steeper slope in winter. To examine the seasonal migration pattern of fish, we visualized the seasonal distribution patterns of Cololabis, Sardinops, Scomber, Seriola and Trachurus, which are genera widely distributed in Japan and have relatively well-known seasonal migration patterns [34,[39][40][41][42][43] (northwards in summer and southwards in winter). In contrast to the well-known seasonal migration, the distributions exhibited unclear seasonal differences (Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…Haghi Vayghan et al 10.3389/fmars.2024.1329254 whereas the main prey of the adult squid is small pelagic fishes. Furthermore, studies have applied primary production data sets in habitat models to evaluate habitat preferences and main fishing grounds in different ecosystem (Liu et al, 2022;Mammel et al, 2022;Mondal et al, 2022;Mondal et al, 2023;Teng et al, 2021;Vayghan and Lee, 2022;Semedi et al, 2023;Zarkami et al, 2023).…”
Section: Figurementioning
confidence: 99%